2016
DOI: 10.1002/adsc.201600410
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Ntert‐Butoxycarbonyl (Boc) Amination by Directed CH Bond Activation

Abstract: N-tert-Butoxycarbonyl azide (BocN 3 ) was shown to be an efficient and economic source for the directed introduction of N-Boc protected amino groups into the thiophene and benzene nucleus. Yields for the amination of 2-pyridin-2-ylthiophenes (10 examples) were 52-88%. For the amination of the respective benzenes (10 examples) yields between 54% and 99% were recorded with an improved reactivity observed for substrates that bear an electron-withdrawing group. The reaction was applied to short total syntheses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 55 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…When 2-naphthyl Weinreb amide was used, the reaction proceeded well with high regioselectivity and a single isomer 2j was formed in 74% yield. Furan or thiophene substrates had been seldom used in the catalytic C–H amination reactions . Interestingly, both furan and thiophene were found to be suitable for this reaction and gave the amination products 2k – m in moderate yield.…”
Section: Resultsmentioning
confidence: 99%
“…When 2-naphthyl Weinreb amide was used, the reaction proceeded well with high regioselectivity and a single isomer 2j was formed in 74% yield. Furan or thiophene substrates had been seldom used in the catalytic C–H amination reactions . Interestingly, both furan and thiophene were found to be suitable for this reaction and gave the amination products 2k – m in moderate yield.…”
Section: Resultsmentioning
confidence: 99%
“…Then, this product was treated with py • HCl under heating conditions to give indoloquinoline 2 in quantitative yield (Scheme 18b). [44] 2-Chloro-3-nitroquinoline 81 was employed as the starting material by reacting with phenylboronic acid via Suzuki crosscoupling, followed by reduction of the nitro group to yield 2phenyl-3-aminoquinoline product 82 in moderate yield. Then, the amino group was subjected to Sandmeyer reaction to give iodoquinoline 83 which was further oxidized using 3-chloroper-oxybenzoic acid in the presence of triflic acid to give benzoquinoloiodolium triflate 84 in excellent yield (96%).…”
Section: Synthesis Of Indoloquinolinesmentioning
confidence: 99%
“…66 They reacted 2,3-dibromoquinoline (58) with 2-(pivaloylamino)phenylboronic acid (59) under palladium(0) catalysis to access biaryl derivative 60, which was cyclized in boiling 25% H 2 SO 4 to afford quindoline (1) in 85% yield. On the other hand, the fluorinated biaryl 61 was also employed, by Bach and co-workers in 2016, 67 as an intermediate in the synthesis of quindoline through the intermediacy of 57. With the knowledge that azides are a good nitrogen source in transition-metal catalysis, 68 they demonstrated that Boc-azide (BocN 3 ) is an efficient and economic source for the directed introduction of N-Bocprotected amino groups into arenes by the use of C-H activation chemistry.…”
Section: Short Review Syn Thesismentioning
confidence: 99%